2022
DOI: 10.1002/cbin.11876
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 influences mitochondrial plasticity and function in hepatic stellate cell activation

Abstract: Caveolin‐1 (Cav‐1) is an integral membrane protein present in all organelles, responsible for regulating and integrating multiple signals as a platform. Mitochondria are extremely adaptable to external cues in chronic liver diseases, and expression of Cav‐1 may affect mitochondrial flexibility in hepatic stellate cells (HSCs) activation. We previously demonstrated that exogenous expression of Cav‐1 was sufficient to increase some classical markers of activation in HSCs. Here, we aimed to evaluate the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Relevant studies have confirmed that CAV-1 plays an integral role in maintaining mitochondrial shape, plasticity, and function, and loss of CAV-1 promotes mitochondrial senescence and dysfunction [ 42 44 ]. Related studies have indicated that CAV-1 in the ER regulates lipid metabolism, ER stress, and maintenance of MAM function.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have confirmed that CAV-1 plays an integral role in maintaining mitochondrial shape, plasticity, and function, and loss of CAV-1 promotes mitochondrial senescence and dysfunction [ 42 44 ]. Related studies have indicated that CAV-1 in the ER regulates lipid metabolism, ER stress, and maintenance of MAM function.…”
Section: Discussionmentioning
confidence: 99%
“…We have added the analyses on Cav1 because this protein was recently reported to play important roles in the glucose metabolic network [ 52 ], lipid metabolism [ 53 ], mitochondrial metabolism [ 54 ], and in cellular metabolic reprogramming [ 55 ]. There is also experimental evidence regarding the role of Ngf in cellular energy homeostasis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal liver tissue, the morphological feature of hepatic stellate cells is the presence of multiple cytoplasmic lipid droplets (LDs). The cave is a small spherical invagination of the plasma membrane, playing an important role in endocytosis, cell transformation, maintaining membrane lipid composition, and signal transduction [52]. CAV-1 is related to the formation of LDs in human hepatic stellate cells, mainly by lateral fissure or cave endocytosis, which transports newly synthesized cholesterol from the endoplasmic reticulum membrane to the plasma membrane vesicles, where it is transported to high-density lipoprotein in the plasma membrane.…”
Section: Cav-1 and Liver Lipid Metabolismmentioning
confidence: 99%